Improving the economic literacy of through livestock business management activities in Kuang Mayung Village - lalita_nyoman2025 (Talenta Publisher Universitas Sumatera Utara, 2025)
The livestock literacy program in Kuang Mayung Hamlet is a strategic initial step in strengthening the capacity of livestock entrepreneurs. This program is intended to increase the insight and skills of residents in managing their livestock businesses more professionally and sustainably. This activity is implemented using an educational and participatory approach, involving residents and guided by the Livestock Technical Implementation Unit (UPT), the Cooperatives and UMKM Office of West Lombok Regency. This activity is carried out entirely through collaboration with the UPT, the Cooperatives and UMKM Office, without the involvement and assistance of university lecturers, as this activity is independent and based on institutional partnerships. The strategies used include direct training, group discussions, and field practice. Through these activities, residents gain new experience and understanding regarding how to manage and care for livestock more appropriately. This activity also serves as an important foundation for the development of an independent and profit-oriented local livestock-based economy.